Serum Lipid Status in Patients with Polycystic Ovary Syndrome - Jahan, Shirin; Islam, Ferdousi; Ashraf, Mohammad Ali; Hossain, Mohammad Zaid; Khan, Md Hasibuddin; Ara, Ismat; Alam, Md Shah; Hoque, Sanaul (Journal of Dhaka Medical College, 2020)
Objective: The aim of this study was to evaluate the serum lipid status in patients with PCOS and to compare the lipid status between PCOS patients and woman without PCOS. Methods: This cross sectional analytical study was carried out in 50 women diagnosed as polycystic ovary syndrome on the basis of Rotterdam Criteria (group I) and 50 women of reproductive age group without polycystic ovary syndrome (group II) attending the outpatient department of Obstetrics and Gynaecology of Dhaka Medical College Hospital, Dhaka during the period of July 2013 to June 2015. Results: The mean total cholesterol, triglycerides and LDL were significantly (p<0.005) higher in group I but mean HDL cholesterol was not significantly (p>0.05) associated with PCOS. Patients with raised total cholesterol : HDL ratio having the risk of developing dyslipidemia estimated to be 11.16 (95% CI = 3.9-33.1) times higher in PCOS patients than that in the group II. In multivariate logistic regression analysis of lipid profile, only raised LDL-C (>130 mg/dl) was found to be significantly associated with PCOS (p<0.05). Conclusion: High LDL level was more associated with PCOS followed by TC, TG and TC:HDL ratio. This study demonstrated a higher level of dyslipidemia specially in PCOS with higher BMI. J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 209-214